Creating and testing a deaf-friendly, stop-smoking Web site intervention. - Jones EG; Goldsmith M; Effken J; Button K; Crago M (American Annals of the Deaf)
Deaf adults' access to smoking cessation programs is limited due to cultural, linguistic, and geographic barriers. Web-based stop-smoking interventions have demonstrated cessation rates comparable to other interventions. The Internet is widely used by Deaf adults, but difficulties with online English text remain. We found no published accounts of Internet interventions promoting smoking cessation among Deaf individuals. The purpose of our project was to create and pilot test a prototype interactive Web site that provides users with information in American Sign Language related to smoking cessation. We utilized web cams to create real-time 'video chat rooms' for virtual support groups and had an 'ask the experts' feature. Deaf community members participated in all phases of development and testing, and a Deaf former smoker served as the moderator for the site. Evaluations were positive, with emphasis on interactive and visual aspects of the site.